Harmonic Characteristics of Variable Frequency System Based on PWM Rectifier - MING Kaiyun (Kongzhi Yu Xinxi Jishu)
In order to solve the problem of harmonic harm of PWM rectifier variable frequency system in power transmission and distribution system, it introduced the basic principle of PWM rectifier control and SPWM modulation according to the main circuit topology of the system, analyzed the main generation mechanism of harmonics and the distribution of harmonic frequency spectrum in the PWM rectifier system through the double Fourier transform, and deduced the influence of modulation depth and transformer leakage inductance on grid side harmonics. Simulation results verified the correctness of the harmonic characteristics analysis.